A new basal rebbachisaurid (Sauropoda, Diplodocoidea) from the Early Cretaceous of the Neuquén Basin; evolution and biogeography of the group - Carballido, José Luis (2012)
Despite that the origin of rebbachisaurids is retrieved as Late Jurassic is not until the upper Lower Cretaceous that this group can be recognised in the fossil record. The group is geographically restricted to Gondwana and Europe, and is particularly diverse in the lower Upper Cretaceous of South America. In this subcontinent, Early Cretaceous forms are solely represented by Amazonsaurus and Zapalasaurus, being the former the putative basalmost rebbachisaurid known. Here, we provide a revised description of the sauropod from the Lohan Cura Formation (Aptian–Albian) that was previously identified as Limaysaurus sp. The new information available (mainly based on new elements) allows us to recognise a new taxon, Comahuesaurus windhauseni gen. et sp. nov. The phylogenetic analysis carried out retrieved this taxon as a relatively basal form of rebbachisaurid, well separated from Limaysaurinae. In this phylogenetic context, the new taxon revealed the presence of a reduced hyposphene–hypantrum system in rebbachisaurids more derived than Histriasaurus, which is completely lost only in Limaysaurinae. Finally, a biogeographical scenario for rebbachisaurids is analysed through the use of a Dispersal, Extinction and Cladogenesis analysis, which retrieves a South American origin for this linage, and a fast dispersion to Africa and Europe during the Hauterivian–Barremian.